2009
DOI: 10.1243/09544054jem1751
|View full text |Cite
|
Sign up to set email alerts
|

Curing characteristics of ceramic stereolithography for an aqueous-based silica suspension

Abstract: The purpose of this paper is to develop the relationships between ceramic stereolithography (SL) process parameters and curing characteristics of a ceramic suspension. A recently developed photocurable aqueous-based silica suspension with high solid loading (50 vol%) was employed to run small batch experiments. Basic structural building units including single line and layer parts were fabricated, based on a new building scheme to establish the predictive equations with the ceramic SL process parameters. The cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Nowadays, CSL is used in medicine for dental and bone healing applications, in microtechnology for the production of microelectromechanical systems (MEMS), sensors, piezoelements and photonic crystals, and also in large scaled applications such as turbine blades or mechanically durable structures. 295] Figures 8 and 9 show ceramic structures generated by CSL and used for several different applications.…”
Section: Stereolithography (Sla)mentioning
confidence: 99%
“…Nowadays, CSL is used in medicine for dental and bone healing applications, in microtechnology for the production of microelectromechanical systems (MEMS), sensors, piezoelements and photonic crystals, and also in large scaled applications such as turbine blades or mechanically durable structures. 295] Figures 8 and 9 show ceramic structures generated by CSL and used for several different applications.…”
Section: Stereolithography (Sla)mentioning
confidence: 99%
“…The density of the laser energy is inversely proportional to the scanning speed, as can be found in equation (1). In the light of the previous findings obtained by Chen et al 19 concerning the relationship between the cured depth of a single layer L d and the laser energy density E 0 , the result was that higher E 0 (namely lower v) led to thicker L d . It was also found that the inadequate scanning speed region was v .…”
Section: Resultsmentioning
confidence: 72%
“…This may be caused by the scattering of the laser light in the ceramic suspension, which has been discussed in the authors' previous article. 19 Significance evaluation and range analysis of each parameter in the SL process. The linear shrinkage results of SL experiments designed in Table 3 were analyzed using the direct analysis Taguchi's Range Analysis method to find the optimum SL parameters combination.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations